14. Abdominal acupuncture reduces pain at spinal level. Issue 12 (December 2016) - Pazzaglia, C.; Testania, E.; Liguori, S.; Coraci, D.; Pecchioli, C.; Padua, L.; Valeriani, M.
Abstract : Abdominal acupuncture (AA) reduces laser-evoked potentials (LEP) amplitude and laser pain perception in healthy subjects (Pazzaglia et al., 2014). The aim of the current study was to investigate the site of AA analgesic effect. We recorded LEPs in 6 healthy volunteers by using 32 EEG scalp electrodes. The experimental protocol included 3 times: (1) baseline, in which LEPs evoked to stimulation of the bilateral dorsal wrist and right foot were recorded before acupuncture; (2) acupuncture, in which LEPs were recorded during AA performed in the abdominal area corresponding to right wrist; (3) rest, in which LEPs were recorded 15 min after the needle removal. Compared to baseline, N2/P2 LEP amplitude evoked by stimulation of both wrists was reduced in the acupuncture and rest times while LEP amplitude evoked by foot stimulation was not modified. Our results suggest that the AA analgesic effect occurs at spinal level.